Attitude Control of Flexible Spacecraft Subject to Disturbances With Time‐Varying Frequencies - Ping, Zhaowu; Gao, Xing; Xu, Delai; Huang, Yunzhi; Jiang, Canghua; Lu, Jun‐Guo (International journal of robust and nonlinear control, 2025)
Recently, the output regulation approach has been successfully applied to solve the disturbance rejection and vibration suppression (DRVS) problem of flexible spacecraft. Although, the DRVS problem can be solved under time‐varying disturbances, the disturbance frequencies should be constants. To remove such limitation, this article further considers the DRVS problem of flexible spacecraft under the external disturbances with time‐varying frequencies. A time‐varying internal model based dynamic state feedback controller is proposed, which can not only solve the DRVS problem of flexible spacecraft under the external disturbances with time‐varying frequencies, but also guarantee the convergence of modal variables. Finally, the effectiveness of the proposed approach is verified by numerical simulation.